Knut Hamsun’s “Meditations on Nansen” Revisited: The Dilemma of Modernity - Eglinger, Hanna (Nordlit, 2015)
Knut Hamsun’s polemic about the Norwegian Nansen cult round 1889 (on the occasion of Fridtjof Nansen’s ski crossing of Greenland), which he published in a newspaper article titled “Meditations on Nansen” (“Nansen-Betragtninger”), was mainly directed against the public enthusiasm for sportive records as a typical modern trend, whose pointless absurdity Hamsun shows in an incisive and specifically provocative way. His critique is primarily aimed at a kind of hero worship that in his opinion is out of all proportion to the uselessness of the expedition’s results. Thus, “a daredevil, well finished adventure, a breakneck act, a sports affair, a lucky strike,” as he outlines Nansen’s venture, becomes the basis for a mass hysteria whose driving forces are invested in the signatures of modernity. The fascination of crossing the line and of extreme forms of progress in “both sports and science”, their entanglement as an example for the “proliferation of hybrids” (Latour 1993), and the contingent dimension of success stories are symptoms of modernity that Hamsun is polemically engaged with. In conclusion, I investigate to what extent Hamsun ironically refers to these symptoms in his novel Editor Lynge (Redakteur Lynge, 1893). My argument is supported by the assumption that Hamsun’s vehement denunciation of such tendencies is owed to the fact that he himself is embroiled in them.